Manual Aspiration Thrombectomy in Acute Myocardial Infarction: A Clinical Experience - Jaiswal, Abhishek; Pollack, Simcha; Chichra, Astha; Moustakakis, Emmanuel; Park, Chong; Kerwin, Todd (International Journal of Angiology, 2016)
Multiple clinical studies have failed to establish the role of routine use of thrombectomy in ST-elevation myocardial infarction (STEMI) patients. There is a paucity of data on the impact of thrombectomy in unselected STEMI patients outside clinical trials. We sought to evaluate the clinical variables and outcomes associated with the performance of thrombectomy in STEMI patients. We retrospectively examined the clinical outcomes in all STEMI patients who underwent successful percutaneous intervention (PCI) at our center. Patients were divided into two groups, one with patients who underwent conventional PCI and another with patients who had thrombus aspiration in addition to conventional PCI. We compared the baseline clinical characteristics, laboratory investigations, re-infarction rates, and all-cause mortality. Total 477 consecutive STEMI patients were identified. Overall, 29% (139) of the patients underwent conventional PCI and 71% (338) of the patients were treated with aspiration thrombectomy and PCI. In addition to the presence of thrombus, patients with nonanterior infarction, and patients with hemodynamic instability requiring intra-aortic balloon pump support were more likely to undergo thrombectomy. Thrombectomy was associated with higher enzymatic infarction (creatine kinase: 2,796 [2,575] vs. 1,716 [1,662]; p < 0.0001; CK-MB: 210.6 [156.0] vs. 142.0 [121.9], p < 0.0001). However, thrombectomy was not associated with any difference in 30 day reinfarction rate (3.3 vs. 2.9%, p = 0.83), mortality (5.0 vs. 7.2%, p = 0.35), or composite of death and 30 day reinfarction (7.7 vs. 9.4%, p = 0.55). We observed that STEMI patients with anterior infarction and hemodynamic instability were more likely to undergo thrombectomy during primary PCI.
Keywords: acute myocardial infarction; angioplasty; atherosclerosis; infarction; myocardial infarction; thrombectomy